PENGELOLAAN KEUANGAN DAN ASET DESA DALAM UPAYA PENGUATAN KELEMBAGAAN PEMERINTAH DESA - Maulidiah, Sri (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2015)
Countryside ever get serious attention and is special the than various component socialize and governmental, so that various component socialize to feel important to do/conduct renewal of about countryside governance. Because during the time arrangement of about countryside united by into Code/Law of about Governance of Area assumed still a lot of there are various form of feebleness and insuffiency in arranging, carrying out and attitude of dynamics of countryside as well as assumed [by] not yet able to quicken countryside development. historically, existence of countryside in Indonesia there have before Negara Kesatuan Republik Indonesia ( NKRI) there is or formed, is such as those which expressed in Rationale of Clarification of Code/Law of Republic Of Indonesia of Number 6 Year 2014 about Countryside, that; " Countryside or so-called by the name of other;dissimilar there is before Totalitarian State of Republic Of Indonesia there is or formed. As evidence from existence of the countryside, can be seen from clarification Section 18 Constitution of Republic Of Indonesia of Year 1945, where there are more or less 250 " Zelfbesturende Landschappen", like Countryside in Java and Bali, Nagari in Minangkabau, Orchard and Clan in Palembang, and others". AN countryside of custom own an function of countryside governance, countryside finance, countryside development, and also get various form of facility and construction from government, governmental of provinsi, and also government of local Town and Regency. In a condition and the position which is like this, hence countryside and countryside of custom will get an same treatment from governmental element and the local local government. One of factor which can strengthen institute of countryside is factor of finance and countryside asset, because finance and asset of countryside will be able to quicken countryside independence, so that need maximal management to finance and countryside asset.